Observations of feeding attempts on Baird’s tapirs (Tapirella bairdii) by common vampire bats (Desmodus rotundus) in Corcovado National Park, Costa Rica - Shipley-Mellon, April; Azofeifa, Alejandro; Herrera, Danny; Solano-Mora, Evelyn T.; Saborío-R, Guido; Olson, Erik R. (Therya Notes, 2024)
Amit and Valverde-Zúñiga reported the first observations of common vampire bats (Desmodus rotundus) attempting to feed on Baird’s tapirs (Tapirella bairdii) in Costa Rica. They reported behaviors they believed to be consistent with anti-parasitism behaviors for the species. We provide additional evidence validating their observations, making the case that such anti-parasitism behaviors may have been selected for and may be widespread within neotropical mammals. As part of a long-term wildlife monitoring and conservation effort, we maintained a camera trap network within Corcovado National Park, Costa Rica since 2015. Our camera trap network consisted of 13 to 56 paired or unpaired cameras placed in a 4 x 4 km grid. In 2021, we captured video footage of one D. rotundus crawling up to a T. bairdii in an apparent feeding attempt as a second D. rotundus appeared to be waiting nearby. The feeding attempt was evaded due to what appears to be behaviors consistent across species, time, and space, suggestive of an evolved behavioral response to feeding attempts by D. rotundus. In 2023, we documented a second event of an apparent feeding attempt by a single D. rotundus on a juvenile T. bairdii walking through our camera’s detection area. Our observation combined with the observations of others suggests that a sudden movement that forces D. rotundus off the body may be an effective strategy for preventing an attack. Some neotropcial wild mammals may have adapted specific avoidance strategies for dealing with D. rotundus.